Multilayer electronic component

The use of polydopamine polymer in the cover part of laminated ceramic capacitors addresses mechanical strength and moisture resistance issues, resulting in improved reliability and durability.

JP2025016336APending Publication Date: 2025-01-31SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024058061
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-18
Filing Date
2024-03-29
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Laminated ceramic capacitors face issues with mechanical strength and moisture resistance due to thin cover portions, leading to cracks and reduced reliability.

Method used

Incorporating a cover part made of polydopamine polymer, which forms a strong bond with ceramic powder and binder, enhancing mechanical strength and moisture resistance by preventing crack propagation and water penetration.

Benefits of technology

The laminated electronic components exhibit improved mechanical strength and humidity resistance, with enhanced reliability and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016336000001_ABST
    Figure 2025016336000001_ABST
Patent Text Reader

Abstract

To provide a multilayer electronic component that excels in mechanical strength and moisture resistance reliability.SOLUTION: A multilayer ceramic capacitor, which is a multilayer electronic component, includes: a body 110 including a capacitance forming section Ac including a dielectric layer 111 and internal electrodes 121, 122 alternately arranged in a first direction, and cover sections 112, 113 arranged on both sides of the capacitance forming section that face each other in the first direction; and external electrodes 131, 132 arranged on the outside of the body and connected to the internal electrodes, with the cover sections containing polydopamine. The polydopamine is a polymer of dopamine and formed by self-polymerization of dopamine, has covalently bonded catechol and imine functional groups, and forms a strong bond with both of an inorganic substance such as ceramic powder and an organic substance such as a binder.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer electronic component. [Background technology]

[0002] Multilayer ceramic capacitors (MLCCs), which are one type of multilayer electronic component, are chip-type capacitors that are mounted on printed circuit boards of various electronic products, such as visual devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones, and mobile phones, and serve to charge and discharge electricity. Multilayer ceramic capacitors can be used as components of various electronic devices due to their advantages of being small in size, high capacity, and easy to mount.

[0003] Recently, multilayer ceramic capacitors have been miniaturized to ensure the capacitance per unit volume of the multilayer ceramic capacitor, and as a result, the thickness of the cover for protecting the capacitance forming part that forms the capacitance of the multilayer ceramic capacitor has been reduced. However, the thinner the cover, the weaker the mechanical strength of the multilayer ceramic capacitor, which may cause cracks or brittle fracture to occur in the multilayer ceramic capacitor. Such cracks, etc., become a path for moisture from the outside to penetrate into the multilayer ceramic capacitor, causing a decrease in the moisture resistance reliability of the multilayer ceramic capacitor.

[0004] Therefore, in order to prevent the mechanical strength and moisture resistance reliability of the multilayer ceramic capacitor from being deteriorated, research is required on a method for improving the hardness and toughness of the cover. Summary of the Invention [Problem to be solved by the invention]

[0005] One of several objects of the present invention is to provide a multilayer electronic component having excellent mechanical strength and moisture resistance reliability.

[0006] However, the scope of the present invention is not limited to the above, and can be more easily understood in the course of describing specific embodiments of the present invention. [Means for solving the problem]

[0007] One embodiment of the present invention provides a laminated electronic component including a main body including a capacitance forming portion including dielectric layers and internal electrodes alternately arranged in a first direction, and cover portions arranged on both sides of the capacitance forming portion facing the first direction, and external electrodes arranged outside the main body and connected to the internal electrodes, wherein the cover portions include polydopamine. Effect of the Invention

[0008] One of the various effects of the present invention is that it can provide a multilayer electronic component having excellent mechanical strength and moisture resistance reliability. [Brief description of the drawings]

[0009] [Figure 1] 1 is a perspective view showing a multilayer electronic component according to an embodiment of the present invention; [Diagram 2] FIG. 2 is an exploded perspective view showing a schematic view of the main body of FIG. [Diagram 3] 2 is a cross-sectional view that illustrates a cross section taken along line II' in FIG. 1. [Figure 4] 2 is a cross-sectional view that shows a schematic cross section taken along line II-II' in FIG. 1. [Diagram 5] FIG. 1 is a schematic diagram illustrating the chemical structures of (a) dopamine hydrochloride, (b) polydopamine polymer, and (c) nitrogen-doped carbonized polydopamine. [Figure 6] FIG. 4 is an enlarged view of the K1 region in FIG. [Figure 7] FIG. 4 is an enlarged view of the K2 region in FIG. [Figure 8]7 is an enlarged view of a region K3 in FIG. 6, and is a schematic diagram showing how a cover portion of the multilayer electronic component according to one embodiment of the present invention suppresses the propagation of a crack. [Figure 9] 4 is a graph showing a schematic analysis result of a cover portion of a multilayer electronic component according to an embodiment of the present invention, using X-ray photoelectron spectroscopy (XPS). [Figure 10] 4 is a graph showing a result of analyzing a cover of a multilayer electronic component according to an embodiment of the present invention using a Raman analysis method. [Figure 11] 1 is a graph showing the results of measuring hardness of a comparative example and an example. [Figure 12] 1 is a graph showing the results of measuring toughness in a comparative example and an example. [Figure 13] 13A is a graph showing the reliability evaluation results of a comparative example, and FIG. 13B is a graph showing the reliability evaluation results of a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shape and size of elements in the drawings may be exaggerated for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.

[0011] In order to clearly explain the present invention in the drawings, parts that are not relevant to the explanation are omitted, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited to those shown in the drawings. Components having the same function within the same concept will be described using the same reference numerals. Furthermore, throughout the specification, when a part is said to "include" a certain component, this does not mean that other components are excluded, but that the part may further include other components, unless otherwise specified.

[0012] In the drawings, the first direction can be defined as a thickness T direction, the second direction can be defined as a length L direction, and the third direction can be defined as a width W direction.

[0013] [Multilayer electronic components] FIG. 1 is a perspective view showing a multilayer electronic component according to an embodiment of the present invention, FIG. 2 is an exploded perspective view showing a main body of FIG. 1, FIG. 3 is a cross-sectional view showing a cross section taken along line I-I' in FIG. 1, FIG. 4 is a cross-sectional view showing a cross section taken along line II-II' in FIG. 1, FIG. 5 is a schematic diagram showing the chemical structures of (a) dopamine hydrochloride, (b) polydopamine polymer, and (c) nitrogen-doped carbonized polydopamine, and FIG. 6 is an enlarged view of the K1 region in FIG. 7 is an enlarged view of area K2 in FIG. 3, and FIG. 8 is an enlarged view of area K3 in FIG. 6, which are schematic diagrams showing how a cover portion of a multilayer electronic component according to one embodiment of the present invention suppresses crack propagation. FIG. 9 is a graph showing schematic results of an analysis of a cover portion of a multilayer electronic component according to one embodiment of the present invention using X-ray photoelectron spectroscopy (XPS). FIG. 10 is a graph showing schematic results of an analysis of a cover portion of a multilayer electronic component according to one embodiment of the present invention using Raman analysis.

[0014] A multilayer electronic component 100 according to one embodiment of the present invention will be described in detail below with reference to Figures 1 to 10. Also, a multilayer ceramic capacitor will be described as an example of the multilayer electronic component, but the present invention is not limited thereto and can be applied to various multilayer electronic components such as inductors, piezoelectric elements, varistors, thermistors, etc.

[0015] The multilayer electronic component 100 according to one embodiment of the present invention may include a body 110 and external electrodes 131 and 132 .

[0016] Although there is no particular limitation on the specific shape of the body 110, the body 110 may have a hexahedral shape or a shape similar thereto, as shown in the drawing. Due to shrinkage of the ceramic powder contained in the body 110 during the firing process and grinding of the corners, the body 110 may have a substantially hexahedral shape, although it is not a hexahedral shape with perfect straight lines.

[0017] The main body 110 may have a first surface and a second surface 1, 2 facing in a first direction, a third surface and a fourth surface 3, 4 connected to the first surface and the second surface 1, 2 and facing in the second direction, and a fifth surface and a sixth surface 5, 6 connected to the first surface to the fourth surface 1, 2, 3, 4 and facing in the third direction.

[0018] The body 110 may include a capacitance-forming portion Ac including dielectric layers 111 and internal electrodes 121, 122 alternately arranged in a first direction. The plurality of dielectric layers 111 forming the capacitance-forming portion Ac are in a fired state, and the boundary between adjacent dielectric layers 111 may be integrated to such an extent that it is difficult to confirm without using a scanning electron microscope (SEM).

[0019] The dielectric layer 111 can be formed by manufacturing a ceramic slurry containing ceramic powder, an organic solvent, and a binder, applying and drying the slurry on a carrier film to provide a ceramic green sheet, and then firing the ceramic green sheet. The ceramic powder is not particularly limited as long as sufficient capacitance can be obtained. For example, barium titanate-based materials, lead composite perovskite-based materials, or strontium titanate-based materials can be used. As examples of the ceramic powder, BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1), Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1), or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc. can be mentioned.

[0020] The internal electrodes 121 and 122 can include a first internal electrode 121 and a second internal electrode 122 that are alternately arranged in the first direction with the dielectric layer 111 interposed therebetween. That is, the first internal electrode 121 and the second internal electrode 122, which are a pair of electrodes having different polarities, can be arranged to face each other with the dielectric layer 111 interposed therebetween. The first internal electrode 121 and the second internal electrode 122 can be electrically separated from each other by the dielectric layer 111 disposed therebetween.

[0021] The first internal electrode 121 is separated from the fourth surface 4 and can be connected to the first external electrode 131 on the third surface 3 side. The second internal electrode 122 is separated from the third surface 3 and can be connected to the second external electrode 132 on the fourth surface 4 side.

[0022] The conductive metal contained in the internal electrodes 121, 122 may be one or more of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof, and more preferably may include Ni, but the present invention is not limited thereto.

[0023] The internal electrodes 121 and 122 may be formed by applying a conductive paste for internal electrodes containing a conductive metal to a predetermined thickness on the ceramic green sheet and firing the same. The method for printing the conductive paste for internal electrodes may be a screen printing method or a gravure printing method, but the present invention is not limited thereto.

[0024] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 do not need to be particularly limited. The average thickness td of the dielectric layer 111 may be, for example, 0.1 μm to 10 μm. The average thickness te of the internal electrodes 121 and 122 may be, for example, 0.1 μm to 3.0 μm. The average thickness td of the dielectric layer 111 and the average thickness of the internal electrodes 121 and 122 can be set arbitrarily according to the desired characteristics and applications. For example, in the case of a high-voltage electric device electronic component to achieve miniaturization and high capacity, the average thickness td of the dielectric layer 111 may be less than 2.8 μm, and the average thickness te of the internal electrodes 121 and 122 may be less than 1 μm. In addition, in the case of a small IT electronic component to achieve miniaturization and high capacity, the average thickness td of the dielectric layer 111 may be 0.4 μm or less, and the average thickness te of the internal electrodes 121 and 122 may be 0.4 μm or less.

[0025] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121, 122 refer to the average size of the dielectric layer 111 and the internal electrodes 121, 122 in the first direction, respectively. The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121, 122 can be measured by scanning the cross sections of the body 110 in the first direction and the second direction with a scanning electron microscope (SEM) with a magnification of 10,000. More specifically, the average thickness td of the dielectric layer 111 can be measured by measuring the thickness at a number of points, for example, 30 points that are equally spaced in the second direction, of one dielectric layer 111, and then averaging the thicknesses. In addition, the average thickness te of the internal electrodes 121, 122 can be measured by measuring the thickness at a number of points, for example, 30 points that are equally spaced in the second direction, of one internal electrode 121, 122, and then averaging the thicknesses. The 30 equally spaced points can be specified by the capacitance forming portion Ac. Meanwhile, by measuring such average values ​​for 10 dielectric layers 111 and 10 internal electrodes 121, 122, respectively, and then measuring the average values, the average thickness td of the dielectric layers 111 and the average thickness te of the internal electrodes 121, 122 can be further generalized.

[0026] The body 110 may include cover parts 112, 113 arranged on both sides of the capacitance forming part Ac facing the first direction. The body 110 may include a first cover part 112 arranged on the first surface 1 side and a second cover part 113 arranged on the second surface 2 side. The cover parts 112, 113 may basically serve to prevent damage to the internal electrodes due to physical or chemical stress. The cover parts 112, 113 may have a similar configuration to the dielectric layer 111, except that they do not include internal electrodes.

[0027] The average thickness tc of the cover parts 112, 113 does not need to be particularly limited. That is, the average thickness tc of the cover parts 112, 113 can be set arbitrarily according to the desired characteristics and applications. For example, in order to reduce the size and increase the capacity of the multilayer electronic component, the average thickness tc of the cover parts 112, 113 may be 300 μm or less, 100 μm or less, 30 μm or less, or 20 μm or less, but the present invention is not limited thereto. Here, the average thickness tc of the cover parts 112, 113 means the average thickness of each of the first cover part 112 and the second cover part 113.

[0028] The average thickness tc of the cover parts 112, 113 may mean the average size of the cover parts 112, 113 in the first direction, and may be the average value of the size in the first direction measured at five equally spaced points on the cross sections of the body 110 in the first and second directions.

[0029] The cover portions 112, 113 can be formed by stacking one or more layers of cover-forming ceramic green sheets, which do not have internal electrode patterns formed thereon, on both sides of the capacitance-forming portion Ac facing the first direction, and then firing the laminate.

[0030] The body 110 may include margin portions 114, 115 arranged on both sides of the capacitance forming portion Ac facing the third direction. The body 110 may include a first margin portion 114 arranged on the fifth surface 5 side and a second margin portion 115 arranged on the sixth surface 6 side. The margin portions 114, 115 may refer to regions between both ends of the internal electrodes 121, 122 and the boundary surface of the body 110 in a cross section obtained by cutting the body 110 in the first and third directions.

[0031] The margin portions 114 and 115 may have a similar configuration to the dielectric layer 111, except that they do not include the internal electrodes 121 and 122. The margin portions 114 and 115 may essentially serve to prevent damage to the internal electrodes 121 and 122 due to physical or chemical stress.

[0032] The margin parts 114, 115 may be formed by applying a conductive paste for internal electrodes to the ceramic green sheet and firing it, except for the places where the margin parts are to be formed. Alternatively, in order to suppress steps due to the internal electrodes 121, 122, the margin parts 114, 115 can be formed by laminating a single dielectric layer or two or more dielectric layers on both sides of the capacitance forming part Ac facing the third direction, after cutting so that the internal electrodes 121, 122 are exposed on the fifth and sixth faces 5, 6 of the main body after lamination.

[0033] The average thickness tm of the margin portions 114, 115 does not need to be particularly limited. That is, the average thickness tm of the margin portions 114, 115 can be set arbitrarily according to the desired characteristics and applications. For example, in order to reduce the size and increase the capacity of the multilayer electronic component, the average thickness tm of the margin portions 114, 115 may be 100 μm or less, 20 μm or less, or 15 μm or less, but the present invention is not limited thereto. Here, the average thickness tm of the margin portions 114, 115 means the average thickness of each of the first margin portion 114 and the second margin portion 115.

[0034] The average thickness tm of the margin portions 114, 115 may mean the average size in the third direction of the margin portions 114, 115, and may be the average value of the sizes in the third direction measured at five equally spaced points in the cross sections of the body 110 in the first and third directions.

[0035] The external electrodes 131, 132 may be disposed outside the body 110 and connected to the internal electrodes 121, 122. The external electrodes 131, 132 may be disposed on the third and fourth surfaces 3, 4 of the body 110 and may extend onto parts of the first, second, fifth and sixth surfaces 1, 2, 5, 6. The external electrodes 131, 132 may include a first external electrode 131 connected to the first internal electrode 121 and a second external electrode 132 connected to the second internal electrode 122.

[0036] The external electrodes 131, 132 are arranged on the third and fourth surfaces 3, 4 of the body 110 and may include first electrode layers 131a, 132a connected to the internal electrodes 121, 122 and second electrode layers 132a, 132b arranged on the first electrode layers 131a, 132a.

[0037] The first electrode layers 131a, 132a may be formed by dipping the third and fourth surfaces 3, 4 of the body 110 into a conductive paste for external electrodes containing a conductive metal and glass, followed by firing. The conductive metal contained in the first electrode layers 131a, 132a may include Cu, Ni, Pd, Pt, Au, Ag, Pb, and / or alloys containing these, but the present invention is not limited thereto.

[0038] Meanwhile, the first electrode layers 131a, 132a may be composed of only one layer including metal and glass, but the present invention is not limited thereto, and the first electrode layers 131a, 132a may have a multi-layer structure. For example, the first electrode layers 131a, 132a may include a first layer including metal and glass, and a second layer disposed on the first layer including metal and resin.

[0039] The metal contained in the second layer is not particularly limited, and may include one or more selected from the group consisting of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof. The resin contained in the second layer may play a role in ensuring bonding and absorbing shock. The resin is not particularly limited as long as it has bonding and shock absorbing properties and can be mixed with metal powder to prepare a paste, and may include, for example, one or more selected from epoxy resin, acrylic resin, ethyl cellulose, etc.

[0040] The second electrode layers 131b, 132b can improve mounting characteristics. The type of the second electrode layers 131b, 132b is not particularly limited, and may be a plating layer containing Ni, Sn, Pd and / or an alloy containing these, or may be formed of multiple layers. The second electrode layers 131b, 132b may be, for example, a Ni plating layer or a Sn plating layer, or may be in a form in which a Ni plating layer and a Sn plating layer are formed in sequence. The second electrode layers 131b, 132b may also include multiple Ni plating layers and / or multiple Sn plating layers.

[0041] In the drawings, the multilayer electronic component 100 is shown to have a structure having two external electrodes 131, 132, but this is not limited to this, and the number and shape of the external electrodes 131, 132 can be changed depending on the shape of the internal electrodes 121, 122 or other purposes.

[0042] According to an embodiment of the present invention, the cover parts 112 and 113 may include polydopamine. Polydopamine is a polymer of dopamine, and polydopamine produced by self-polymerization of dopamine has covalently bonded catechol and imine functional groups, and can form strong bonds with both inorganic materials such as ceramic powder and organic materials such as binders.

[0043] Dopamine hydrochloride shown in FIG. 5(a) may be added to the ceramic green sheet for forming the cover part according to an embodiment of the present invention. The dopamine hydrochloride added to the ceramic green sheet for forming the cover part may form a polydopamine polymer shown in FIG. 5(b) by self-polymerization. The ceramic green sheet for forming the cover part may form a strong bond with the ceramic powder or binder contained in the ceramic green sheet for the cover part by including the polydopamine polymer, thereby improving the adhesive strength of the ceramic green sheet for the cover part. Therefore, when the ceramic green sheets for forming the cover part are laminated to form the cover parts 112 and 113, delamination or cracks between the sheets may be prevented, and the heat and pressure applied in the lamination and compression process may be reduced.

[0044] All or a part of the polydopamine polymer contained in the ceramic green sheet for the cover may be converted into nitrogen-doped graphenated polydopamine as shown in FIG. 5(c) by undergoing a sintering process for forming the body of the multilayer electronic component 100. In one embodiment, at least a part of the polydopamine contained in the cover parts 112 and 113 may be nitrogen-doped graphenated polydopamine. The nitrogen-doped graphenated polydopamine contained in the cover parts 112 and 113 is a two-dimensional material and may improve the elastic modulus and toughness of the cover parts 112 and 113, and may play a role in blocking the propagation of cracks generated in the cover parts 112 and 113. As a result, the mechanical strength of the multilayer electronic component 100 may be improved, and ultimately the moisture resistance reliability of the multilayer electronic component 100 may be improved.

[0045] In one embodiment, the nitrogen content (at%) of the total content (at%) of elements constituting the cover parts 112, 113 may be greater than 0 at% and less than or equal to 3 at%. The nitrogen of the elements constituting the cover parts 112, 113 may be derived from nitrogen-doped carbonized polydopamine. If the nitrogen content of the total content (at%) of elements constituting the cover parts 112, 113 exceeds 3 at%, the polydopamine content becomes excessive, which may cause brittle fracture due to the formation of agglomerates.

[0046] There is no particular limitation on the method for measuring the nitrogen content (at%) of the total content of elements constituting the cover parts 112 and 113. For example, after obtaining a measured image by scanning the cross section of the main body 110 in the first and second directions with a transmission electron microscope (TEM) or a scanning electron microscope (SEM), five points in the image that are equally spaced in the second direction in the cover parts 112 and 113 are analyzed with energy dispersive spectroscopy (EDS) to calculate the average value of the nitrogen content (at%) of the total content (100 at%) of elements constituting the cover parts 112 and 113 in each point, thereby measuring the nitrogen content.

[0047] The cover parts will be described in more detail below with reference to Fig. 6. Fig. 6 shows an enlarged view of a portion of the second cover part 113, but since the first cover part 112 and the second cover part 113 have substantially the same configuration, the following description will be deemed to include all descriptions of the first cover part 112 and the second cover part 113.

[0048] 6, the cover portion 113 includes a plurality of dielectric crystal grains G1 and grain boundaries GB1 disposed between adjacent dielectric crystal grains G1, and the polydopamine included in the cover portion 113 may be disposed at the grain boundaries GB1. The polydopamine disposed at the grain boundaries GB1 may effectively block the propagation of cracks. In addition, since the nitrogen-doped carbonized polydopamine is hydrophobic, when the nitrogen-doped carbonized polydopamine is located at the grain boundaries GB1, it may act as a barrier against moisture penetration.

[0049] Referring to FIG. 8, when the crack CR propagates toward the grain boundary GB1 existing between the dielectric grains G1, τs (τs=μN R Here, forces such as μ (dynamic friction) can be consumed as energy. In this case, if polydopamine with a high elastic modulus is present at the grain boundary GB1, the μ value can increase. In other words, if polydopamine with a high elastic modulus is present at the grain boundary GB1, more energy is consumed for the propagation of the crack CR, so that the crack propagation can be effectively blocked.

[0050] Meanwhile, the nitrogen-doped carbonized polydopamine disposed at the grain boundary GB1 may suppress the grain growth of the crystal grains G1 and induce densification of the cover portion 113. The average size of the plurality of dielectric crystal grains G1 included in the cover portion 113 may be, for example, 170 nm or more and 200 nm or less.

[0051] Meanwhile, as shown in FIG. 7, the dielectric layer 111 may include a plurality of dielectric crystal grains G2 and a grain boundary GB2 disposed between adjacent dielectric crystal grains G2. The average size of the plurality of dielectric crystal grains G2 included in the dielectric layer 111 does not need to be particularly limited. The average size of the plurality of dielectric crystal grains G2 included in the dielectric layer 111 may be larger than the average size of the plurality of dielectric crystal grains G1 included in the cover portion 113. In this case, there may be an advantage in terms of improving the capacity of the multilayer electronic component 100. However, the present invention is not limited thereto, and the average size of the plurality of dielectric crystal grains G2 included in the dielectric layer 111 may be smaller than the average size of the plurality of dielectric crystal grains G1 included in the cover portion 113. In this case, there may be an advantage in terms of improving the reliability of the multilayer electronic component 100.

[0052] The average size of the plurality of dielectric crystal grains G1 contained in the cover portion 113 may refer to an average value of the size of the dielectric crystal grains obtained by, for example, obtaining an image of the central region of the cover portion 113 (e.g., region K1 in FIG. 3) at 50,000 times magnification with a scanning electron microscope (SEM) in a cross section in the first and second directions cut at the center of the second direction of the body 110, and then analyzing the image using an image analysis program, for example, Zootos Program by Zootos Corporation.

[0053] In addition, the average size of the plurality of dielectric crystal grains G2 contained in the dielectric layer 111 may refer to an average value of the dielectric crystal grain size obtained by obtaining an image of the dielectric layer 111 arranged in the central region of the capacitance forming portion Ac (e.g., region K2 in FIG. 3) at a magnification of 50,000 times using a scanning electron microscope (SEM) in a cross section in the first and second directions cut at the center of the second direction of the body 110, and then analyzing the image using an image analysis program, for example, Zootos Program by Zootos Corporation.

[0054] Referring to FIG. 9, in one embodiment, the cover units 112 and 113 may have an N1s peak and a C1s peak when analyzed using X-ray photoelectron spectroscopy (XPS). When the cover units 112 and 113 include nitrogen-doped carbonized polydopamine, an N1s peak may be detected in addition to Ba3d5, O1s, Ti2p, and C1s peaks. That is, when the N1s and C1s peaks are simultaneously detected during the XPS analysis, it may be determined that the cover units 112 and 113 contain nitrogen-doped carbonized polydopamine. Meanwhile, the intensity of the N1s peak may have a maximum value at a binding energy of 395 eV to 405 eV, and the intensity of the C1s peak may have a maximum value at a binding energy of 280 eV to 290 eV, but the present invention is not limited thereto.

[0055] The XPS analysis of the cover parts 112, 113 may be performed on the outer surfaces of the cover parts 112, 113, but the present invention is not limited to this, and may also be performed on cross sections in the first and second directions polished up to the center of the main body 110 in the third direction.

[0056] Referring to FIG. 10, in one embodiment, during Raman analysis of the cover portions 112 and 113, -1 From 1380cm -1 The first peak X was detected at a Raman shift of 1610 cm -1 From 1630cm -1 The second peak Y can be detected by the Raman shift of the first peak X. The first peak X can represent the D peak, and the second peak Y can represent the G peak. The first peak X and the second peak Y appear simultaneously during the Raman analysis of the cover parts 112 and 113 because the cover parts 112 and 113 have a carbonized polydopamine structure having a two-dimensional structure.

[0057] In one embodiment, the ratio of the maximum intensity of the first peak X to the maximum intensity of the second peak Y may be 0.01 or more and 1.50 or less. The ratio of the maximum intensity of the first peak X to the maximum intensity of the second peak Y may vary depending on the defects in the carbonized polydopamine and the degree of nitrogen doping.

[0058] In one embodiment, the full width at half maximum of the first peak X is 80 cm -1 More than 90cm -1 The full width at half maximum of the second peak Y is 100 cm or less. -1 More than 110cm -1 The full width at half maximum can be the width of a peak at half the maximum intensity of the peak. The full width at half maximum of the first peak X and the second peak Y can be different depending on the defects in the carbonized polydopamine and the degree of nitrogen doping.

[0059] The Raman analysis of the cover portions 112, 113 can be performed on the outer surfaces of the cover portions 112, 113, but the present invention is not limited to this and can also be performed on cross sections in the first and second directions polished up to the center of the main body 110 in the third direction.

[0060] In one embodiment, the dielectric layer 111 does not need to contain polydopamine. When the dielectric layer 111 contains polydopamine, the mechanical strength of the dielectric layer 111 can be improved. However, when polydopamine is contained in the dielectric layer 111, which is directly related to the electrical properties of the multilayer electronic component 100, side effects such as a deterioration in the breakdown voltage of the multilayer electronic component 100 may occur.

[0061] When the dielectric layer 111 does not contain polydopamine, nitrogen may not be detected in the dielectric layer 111. In addition, when the dielectric layer 111 is analyzed using X-ray photoelectron spectroscopy (XPS), an N1s peak may not be detected. In addition, when the dielectric layer 111 is analyzed using Raman spectroscopy, an N1s peak may not be detected at 1360 cm -1 From 1380cm -1 Raman shift and 1610cm -1 From 1630cm -1At least one of the Raman shifts may not detect a peak.

[0062] In one embodiment, the dielectric layer 111 may contain a polydopamine content that is less than the content of polydopamine contained in the cover portions 112 and 113. When polydopamine is added to the dielectric layer 111 to improve the mechanical strength of the dielectric layer 111, it is preferable to add a polydopamine content that is less than the content of polydopamine contained in the cover portions 112 and 113 to the dielectric layer 111 in order to prevent deterioration of the electrical characteristics of the multilayer electronic component 100. When the dielectric layer 111 contains polydopamine, the polydopamine may be disposed at the grain boundaries GB2 of the dielectric layer 111.

[0063] When the dielectric layer 111 contains polydopamine, a Raman spectrum of the dielectric layer 111 is obtained at 1360 cm -1 From 1380cm -1 A third peak was detected at the Raman shift of 1610 cm -1 From 1630cm -1 A fourth peak may be detected by the Raman shift of 1 / 100 of the dielectric layer 111. Meanwhile, since the dielectric layer 111 contains polydopamine at a content lower than the content of polydopamine contained in the covers 112 and 113, the intensity of the third peak may be lower than the intensity of the first peak X, and the intensity of the fourth peak may be lower than the intensity of the second peak Y, but the present invention is not limited thereto.

[0064] (Experimental Example) <Sample Preparation> BaTiO3 powder, an organic solvent such as ethanol, and a binder such as polyvinyl butyral were mixed to prepare a ceramic slurry, which was then coated on a carrier film and dried to prepare a ceramic green sheet. Next, a conductive paste for an internal electrode, which contains Ni powder and a binder, was applied to a predetermined thickness on the ceramic green sheet.

[0065] Next, ceramic green sheets for the cover portion on which no internal electrode pattern is formed are laminated, and then a conductive paste for the internal electrodes is printed to laminate tens to hundreds of ceramic green sheets on which the internal electrode pattern is formed. Finally, ceramic green sheets for the cover portion on which no internal electrode pattern is formed are laminated, and then the main body is formed by performing a compression bonding, cutting and firing process.

[0066] In this case, in the comparative example, dopamine hydrochloride was not added to the ceramic slurry for forming the ceramic green sheet for the cover part. In the example 1, 0.5 parts by weight of dopamine hydrochloride was added to 100 parts by weight of the total ceramic slurry for forming the ceramic green sheet for the cover part. In the example 2, 1 part by weight of dopamine hydrochloride was added to 100 parts by weight of the total ceramic slurry for forming the ceramic green sheet for the cover part.

[0067] Next, the main body was dipped in a conductive paste made of a mixture of Cu powder, glass frit, binder and solvent, and then fired to form a first electrode layer, and a Ni plating layer and a Sn plating layer were sequentially formed on the first electrode layer to form a second electrode layer. Thus, the sample chips of the comparative example, the example 1 and the example 2 were prepared.

[0068] <Evaluation of hardness and toughness> Then, the hardness and toughness of the cover of each sample were evaluated. The hardness and toughness of the cover were measured on the outer surface of the cover using a Vickers hardness tester, and 20 sample tips each of the comparative example, example 1, and example 2 were subjected to the test.

[0069] FIG. 11 is a graph showing the results of measuring the hardness of the comparative example and the example, and FIG. 12 is a graph showing the results of measuring the toughness of the comparative example and the example.

[0070] 11 and 12, it can be seen that Example 1 and Example 2 have better hardness and toughness than Comparative Example. Meanwhile, samples in which 1 part by weight or more of dopamine hydrochloride was added to 100 parts by weight of the total ceramic slurry for forming the ceramic green sheet for the cover were also evaluated in the same manner, but the hardness and toughness values ​​could not be measured due to brittle fracture of the sample chip. This is expected to be due to the influence of agglomerates generated by the excessive content of dopamine hydrochloride.

[0071] <Evaluation of Moisture Resistance Reliability> Thereafter, evaluation of moisture resistance reliability was performed on the sample chip of the comparative example and the sample chip of Example 2. The evaluation of moisture resistance reliability was performed on 400 each of the sample chips of the comparative example and Example 2, by applying a voltage of 3.75 V at a temperature of 85° C. and a humidity of 85% for 8 hours, and then measuring the change in insulation resistance IR.

[0072] 13 is a graph showing (a) the reliability evaluation results of the comparative example and (b) the reliability evaluation results of Example 2. Referring to Fig. 13, it can be seen that the comparative example has a sample in which the insulation resistance IR drops sharply at the beginning compared to Example 2. That is, it can be seen that Example 2 has better moisture resistance reliability than the comparative example because the hydrophobic nitrogen-doped carbonized polydopamine is located at the grain boundaries and acts as a barrier against moisture penetration.

[0073] The present invention is not limited by the above-described embodiments and the accompanying drawings, but is limited by the scope of the accompanying claims. Therefore, within the scope of the technical idea of ​​the present invention described in the claims, various substitutions, modifications and changes are possible by a person having ordinary knowledge in the art, and these also belong to the scope of the present invention.

[0074] In addition, the expression "one embodiment" does not mean the same embodiment, but is provided to emphasize and describe each different unique feature. However, one embodiment presented above does not exclude being realized in combination with features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, unless there is a description that is opposite or contradictory to the matter in the other embodiment.

[0075] Furthermore, expressions such as "first, second" are used to distinguish one component from another and do not limit the order and / or importance of the components. In some cases, the first component may be named the second component, and similarly the second component may be named the first component, within the scope of the rights. [Explanation of symbols]

[0076] 100: Multilayer electronic components 110: Main unit 111: Dielectric layer 112, 113: Cover part 114, 115: Margin 121, 122: Internal electrode 131, 132: External electrode 131a, 132a: first electrode layer 131b, 132b: Second electrode layer G1, G2: Grain GB1, GB2: Grain boundary

Claims

1. a main body including a capacitance forming portion including dielectric layers and internal electrodes alternately arranged in a first direction, and cover portions arranged on both sides of the capacitance forming portion facing each other in the first direction; an external electrode disposed outside the body and connected to the internal electrode; The multilayer electronic component, wherein the cover portion contains polydopamine.

2. 2. The multilayer electronic component according to claim 1, wherein at least a portion of the polydopamine contained in the cover is carbonized polydopamine doped with nitrogen.

3. 3. The multilayer electronic component according to claim 1, wherein a nitrogen content (at %) of a total content (at %) of elements constituting said cover portion is more than 0 at % and is 3 at % or less.

4. the cover portion includes a plurality of dielectric crystal grains and grain boundaries disposed between adjacent dielectric crystal grains; 3. The multilayer electronic component according to claim 1, wherein the polydopamine contained in the cover is disposed at the crystal grain boundaries.

5. the cover portion includes a plurality of dielectric crystal grains and grain boundaries disposed between adjacent dielectric crystal grains; 3. The multilayer electronic component according to claim 1, wherein an average size of the plurality of dielectric crystal grains contained in the cover portion is not less than 170 nm and not more than 200 nm.

6. 3. The multilayer electronic component according to claim 1, wherein an N1s peak and a C1s peak are detected in the cover portion when the cover portion is analyzed using X-ray photoelectron spectroscopy.

7. During Raman analysis of the cover, -1 From 1380 cm -1 The first peak was detected at a Raman shift of 1610 cm -1 From 1630 cm -1 The multilayer electronic component according to claim 1 or 2, wherein the second peak is detected at a Raman shift of

8. 8. The multilayer electronic component according to claim 7, wherein a ratio of a maximum intensity of the first peak to a maximum intensity of the second peak is equal to or greater than 0.01 and equal to or less than 1.

50.

9. The full width at half maximum of the first peak is 80 cm -1 90cm or more -1 The full width at half maximum of the second peak is 100 cm or less. -1 110cm or more -1 8. The multilayer electronic component according to claim 7, wherein:

10. 3. The multilayer electronic component according to claim 1, wherein the dielectric layer does not contain polydopamine.

11. 3. The multilayer electronic component according to claim 1, wherein the dielectric layer contains a polydopamine content that is less than a content of polydopamine contained in the cover portion.

12. 3. The multilayer electronic component according to claim 1, wherein, in an analysis using X-ray photoelectron spectroscopy, an N1s peak is detected in the cover portion, but an N1s peak is not detected in the dielectric layer.

13. During Raman analysis, the cover has a wavelength of 1360 cm -1 From 1380 cm -1 The first peak was detected at a Raman shift of 1610 cm -1 From 1630 cm -1 A second peak was detected at the Raman shift of 1360 cm -1 From 1380 cm -1 Raman shift and 1610 cm -1 From 1630 cm -1 3. The multilayer electronic component according to claim 1, wherein no peak is detected in at least one of the Raman shifts.

14. During Raman analysis, the cover has a wavelength of 1360 cm -1 From 1380 cm -1 The first peak was detected at a Raman shift of 1610 cm -1 From 1630 cm -1 A second peak was detected at the Raman shift of 1360 cm -1 From 1380 cm -1 A third peak was detected at the Raman shift of 1610 cm -1 From 1630 cm -1 The fourth peak was detected at the Raman shift of 3. The multilayer electronic component according to claim 1, wherein an intensity of the third peak is lower than an intensity of the first peak, and an intensity of the fourth peak is lower than an intensity of the second peak.